The Influence of Communication, Organizational Culture and Work from Home on the Performance of Banking Sector Employees in Jakarta - Mohamad Ramadhan Argakoesoemah (Yayasan Adra Karima Hubbi, 2024)
This study aims to identify the influence of communication, organizational culture, and work from home on the performance of employees in the banking sector in Jakarta. The independent variables in this study are Communication, Organizational Culture, and Work from Home. While, the dependent variable in this study is Employee Performance. Hypothesis testing in this study uses the SEM (Structural Equation Modelling) method, which is supported by IBM SPSS AMOS 22 and IBM SPSS Statistics 26 application devices. The data collection technique in this study used an online questionnaire with the Google Form application to collect information on respondents, who were employees in the banking sector in Jakarta during the Covid-19 pandemic conditions. The results of this study indicate that: 1) Communication has a positive and significant effect on Employee Performance; 2) Organizational Culture does not have an effect on Employee Performance; 3) Work from Home does not have an effect on Employee Performance